Virtual Reality as a Tool in Pulmonary Rehabilitation: A Narrative Review - Sumedha, .; Clements, Jim Brown; Vinosh Kumar, Purushothaman (INTI International University, 2020)
Background and Objective: Pulmonary Rehabilitation (PR) has been widely accepted as a standard non-pharmacological intervention for the management of chronic lung diseases. The 21st century has ushered in the age of technology utilization in every field including healthcare. Virtual Reality (VR) is an emerging technology with several potential benefits in almost every aspect of PR, whether be it assessment or treatment. This narrative review aims to explore emerging evidence regarding the utilization of VR in PR, adding feathers to the emerging IR4.0.